Roxanna Slade - Price, Reynolds 1933-2011 (Scribner, 1998)
An old woman born in 1900 reflects on the joys and sorrows of her long life, commenting on them with wisdom. She is Roxanna Slade, matriarch of a rural family, and her story gives a portrait of the South before the great changes.
Keywords: City and town life -- Fiction; Older women -- Fiction; North Carolina -- Fiction; Domestic fiction